Potential Stunting in Riverside Peoples (Study on Pahandut Urban Village, Palangka Raya City) - Shinta, Herlina Eka; Utami, Purnama Julia; Adiwijaya, Saputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine the potential occurrence of stunting for residents who live on the river side, especially residents who live and inhabit the Kahayan River. And the subject is women who are pregnant, have a toddler. The study was conducted with a qualitative method, a descriptive approach used to explain stunting potential for people who live on riverside. This study uses purposive sampling, data collection techniques used: interviews, observation and documentation. The findings of this study are the environmental health conditions of people who live on riverside are very bad, if it refers to WHO standards, because there are no adequate sanitation facilities related to water management and disposal of solid and liquid waste, plus the habits of people who still throw garbage directly into the river. Environmental health in the community should be improved through collaboration of various institutions, in process to change the behavior patterns of disposing of garbage in the river.Â  Second Findings the potential for stunting in the riverside communities is quite large, because the majority of peoples doesnâ€™t count nutritional content in food, so awareness and empowerment should be done. So that in the future there will be an increase in the quality of health of children, mothers and adolescents.